Planning ethically responsible research - Sieber, Joan E. (Applied social research methods series ;, 2013)
This book guides readers through one of the most important aspects of their social or behavioural research: planning ethically responsible research. The authors offer practical guidance in each chapter for satisfying federal regulations governing human research and for working with the university's Institutional Review Board (IRB). The book includes an abundance of useful tools: detailed instructions on development of an effective IRB protocol; methods for handling issues of consent, privacy, confidentiality and deception; ways to assess risk and benefit to optimize research outcomes; and how to respect the needs of vulnerable research populations. The book is an invaluable guide to help researchers and graduate students understand ethical concerns within real-life research situations.